The Cytosolic Adaptor AP‐1A Is Essential for the Trafficking and Function of Niemann‐Pick Type C Proteins. (20th February 2013) - Poirier, Steve; Mayer, Gaétan; Murphy, Stephanie R.; Garver, William S.; Chang, Ta Yuan; Schu, Peter; Seidah, Nabil G.
<x xml:space="preserve">Abstract</x> Niemann‐Pick type C (NPC) disease is a fatal neurodegenerative disorder characterized by over‐accumulation of low‐density lipoprotein‐derived cholesterol and glycosphingolipids in late endosomes/lysosomes (LE/L) throughout the body. Human mutations in either NPC1 or NPC2 genes have been directly associated with impaired cholesterol efflux from LE/L. Independent from its role in cholesterol homeostasis and its NPC2 partner, NPC1 was unexpectedly identified as a critical player controlling intracellular entry of filoviruses such as Ebola. In this study, a yeast three‐hybrid system revealed that the NPC1 cytoplasmic tail directly interacts with the clathrin adaptor protein AP‐1 via its acidic/di‐leucine motif. Consequently, a nonfunctional AP‐1A cytosolic complex resulted in a typical NPC‐like phenotype mainly due to a direct impairment of NPC1 trafficking to LE/L and a partial secretion of NPC2. Furthermore, the mislocalization of NPC1 was not due to cholesterol accumulation in LE/L, as it was not rescued upon treatment with Mβ‐cyclodextrin, which almost completely eliminated intracellular free cholesterol. Our cumulative data demonstrate that the cytosolic clathrin adaptor AP‐1A is essential for the lysosomal targeting and function of NPC1 and NPC2.